1998
DOI: 10.1002/jlb.64.3.351
|View full text |Cite
|
Sign up to set email alerts
|

A 70-kDa amino-terminal fibronectin fragment supports gelatin binding to macrophages and decreases gelatinase activity

Abstract: We previously reported that a macrophage response that increased binding to 125

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Several studies suggest that the interactions between HS-binding proteins and heparan sulfate proteoglycans could regulate their biological activities (57,58) and orientate them toward their target cell (59,60) at the site of the inflammatory reaction. The expression of CS/DSPGs is differentially regulated in human endothelial cells by inflammatory cytokines (7), and DS released in vivo after injury can support FGF-2-mediated cell proliferation (6). Interestingly, endocan, a DSPG devoid of any effect on coagulation, is also secreted by human vascular endothelial cells, and we have demonstrated previously (39,40) that the secretion of endocan is under the control of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Several studies suggest that the interactions between HS-binding proteins and heparan sulfate proteoglycans could regulate their biological activities (57,58) and orientate them toward their target cell (59,60) at the site of the inflammatory reaction. The expression of CS/DSPGs is differentially regulated in human endothelial cells by inflammatory cytokines (7), and DS released in vivo after injury can support FGF-2-mediated cell proliferation (6). Interestingly, endocan, a DSPG devoid of any effect on coagulation, is also secreted by human vascular endothelial cells, and we have demonstrated previously (39,40) that the secretion of endocan is under the control of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 68%
“…Heparan sulfate proteoglycans have come to particular prominence recently because of their multiple regulatory interactions with growth factors, enzymes, enzyme inhibitors, and components of the extracellular matrix (4,5). Dermatan sulfate proteoglycans (DSPGs) 1 from human fluids become of particular importance during inflammation and response to injury (6 -11), contributing, for example, to the majority of the FGF-2-dependent cell proliferation involved in the regulation of wound repair (6). DSPGs are also known to bind to many HS-binding proteins, including FGF-2, interleukin-7 (12), platelet factor 4 (13), fibronectin (14), and heparin cofactor II (15).…”
mentioning
confidence: 99%
“…Previous studies that attempted to elucidate the in vitro effect of FN fragments on cell behavior used one isolated FN fragment, which was obtained commercially, often originating from the N terminus of the molecule [29,37,38]. However, such an approach does not take into consideration the fact that monocytes respond to the integrated sum of all signals provided by the mixture of different FN fragments.…”
Section: Discussionmentioning
confidence: 98%
“…During wound healing, a large number of monocytes are quickly recruited into the site of injury, and they play a crucial role in orchestrating the subsequent tissue repair 1–3. Monocyte/macrophage response to the extracellular matrix (ECM) components such as fibronectin, collagen, and gelatin is an active field of research 4–7. Some of these ECM proteins contain proline‐histidine‐serine‐arginine‐asparagine (PHSRN) and conserved motifs such as arginine‐glycine‐aspartic acid (RGD) that allow monocyte integrin‐mediated cell attachment, focal contact formation, motility, and protein expression 8–11.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Monocyte/macrophage response to the extracellular matrix (ECM) components such as fibronectin, collagen, and gelatin is an active field of research. [4][5][6][7] Some of these ECM proteins contain proline-histidine-serine-arginine-asparagine (PHSRN) and conserved motifs such as arginine-glycine-aspartic acid (RGD) that allow monocyte integrin-mediated cell attachment, focal contact formation, motility, and protein expression. [8][9][10][11] RGD has been utilized extensively to modify biomaterials to promote integrin-mediated cell attachment and we have previously demonstrated that RGD grafted onto an ECM-based semi-interpenetrating network (sIPN) enhances cell adhesion and modulates signaling, and cytokine and gene expression.…”
Section: Introductionmentioning
confidence: 99%